Design, simulation and applications of inductors and transformers for Si RF ICs - Niknejad, Ali M., 1972- (Kluwer international series in engineering and computer science. Analog circuits and signal processing., 2000)
Wireless RF and microwave ICs depend critically on passive devices, such as inductors, capacitors, and transformers. Passive devices allow the optimization of key RF circuit building blocks by minimizing noise, maximizing gain and frequency of operation, and minimizing power. The integration of passive devices on the Si IC substrate requires a critical understanding of substrate coupling and loss, including electrically induced conductive and displacement current flowing in the substrate as well as magnetically induced eddy currents. Design, Simulation and Applications of Inductors and Transformers for Si RF ICs provides a deep understanding of the physics involved in the operation of these devices at microwave frequencies. Additionally, the book tackles two critical blocks that depend critically on the passive devices, the voltage-controlled oscillator and a distributed amplifier. Design, Simulation and Applications of Inductors and Transformers for Si RF ICs will be of interest to RF and microwave integrated circuit engineers, computer aided designers, device physicists, and electromagnetic researchers, as well as power electronics engineers.